Entourage [videorecording (DVD)] - Ellin, Doug; Connolly, Kevin, 1974-; Grenier, Adrian, 1976-; Dillon, Kevin ([Publisher not identified], 2015)
Movie star Vincent Chase, together with his boys, Eric, Turtle, and Johnny, is back, and back in business with super agent turned studio head Ari Gold. Some of their ambitions have changed, but the bond between them remains strong as they navigate the capricious and often cutthroat world of Hollywood.